An Environmental Justice Perspective on Smallholder Pesticide Use in Sub-Saharan Africa. (March 2021) - Isgren, Ellinor; Andersson, Elina
Pesticide use is increasing in many parts of sub-Saharan Africa, and many smallholders purchase, handle, and apply toxic pesticides with inadequate equipment, knowledge, and technical support. Through the frame of environmental justice, this literature-based study analyzes characteristics, impacts, and drivers of smallholder pesticide use in sub-Saharan Africa, with particular attention to Uganda as a case. We find that market liberalization, poor regulation enforcement, and persistent neglect of agricultural extension place the burden of risk largely on farmers, while perceived necessity of pesticides and the elusive nature of impacts (especially under conditions of insufficient monitoring) likely delay social mobilization around pesticides. The environmental justice frame, which has seen limited application in smallholder contexts, importantly helps delineate future directions for research and practice. It is particularly effective for redirecting focus from highly limited managerial solutions for "safe use" toward deeper problem drivers and solutions capable of tackling them.